Partial purification and characterization of trehalase from axenically grown myxamoebae of Dictyostelium discoideum - Gupta, Jyothi; Cotter, David Allen (Biochimica et biophysica acta, 1990)
Lysosomal trehalase from the myxamoebae of Dictyostelium discoideum has been partially purified. The behavior of the enzyme under different chromatographic and electrophoretic conditions reveals its close similarities to other lysosomal enzymes that have been studied earlier. The cellular trehalase, which is electrophoretically homogenous, appears as two peaks of activity when subjected to hydroxypatite and gel filtration chromatography. The enzyme has isoelectric points of 4.0 and < 2.5. Among natural disaccharides tested, the purified trehalase showed absolute specificity for trehalose with an apparent K m of 1.15 mM. However, the enzyme efficiently utilized the synthetic sugar α- d-glucosyl fluoride as a substrate. Various methods were employed to estimate the apparent molecular weight, which was found to lie in the range of 30–162 kDa.